Aerospace series. Heat-resisting alloy NI-PH1301 (NiCr19Co18Mo4Ti3Al3). Solution treated and precipitation treated. Bars and sections. De ≤ 200 mm. (30th March 2023) - British Standards Institution,
No abstract available